MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA OPERASI PEMBAGIAN BILANGAN CACAH MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION: (Penelitian Tindakan Kelas pada Siswa Kelas III SDN 2 Setiamulya Kecamatan Tamansari Kota Tasikmalaya) - Dila Aulia; Winarti Dwi Febriani; Geri Syahril Sidik (STKIP Subang, 2025)
This research is motivated by students' limited understanding of the mathematical concept of whole number division. This is caused by the lack of variety in the learning approach and students' difficulties in applying concepts to solve mathematical problems. This research aims to improve the mathematical concept understanding ability of grade III students of SD Negeri 2 Setiamulya in the material of whole number division through the application of the Realistic Mathematics Education (RME) approach. This study was a Classroom Action Research (CAR) conducted in two cycles, with research subjects comprising 22 students from grade III of SD Negeri 2 Setiamulya. Each cycle follows the stages of the CAR model of Kemmis and McTaggart, which consists of four stages: planning, implementation, observation, and reflection. The data collection techniques employed included tests, observation, and documentation. The research instruments consist of observation sheets of teacher and student activities, as well as a conceptual understanding test instrument. The study's results show an increase in students' comprehension of mathematical concepts in each cycle. In the pre-action phase, the average student score was 55.22, with a learning completion percentage of 40.9%, which fell into the “Poor” category. After the implementation of the RME approach, the average score in cycle I increased to 78.18 with a completion percentage of 72.7% included in the “Good” category, and cycle II, the average score increased again to 85 with a completion percentage of 86.4% included in the “Very Good” category. Thus, it can be concluded that the implementation of the Realistic Mathematics Education (RME) approach is effective in improving students' comprehension of mathematical concepts in the division of whole numbers material.